1995
DOI: 10.1128/iai.63.9.3514-3519.1995
|View full text |Cite
|
Sign up to set email alerts
|

Roles of gamma interferon and interleukin-4 in genetically determined resistance to Coccidioides immitis

Abstract: The profiles of gamma interferon (IFN-␥) and interleukin-4 (IL-4) production were evaluated during the course of coccidioidomycosis in two inbred mouse strains which differ in their susceptibility to Coccidioides immitis. Cytokine responses, measured at the molecular and protein levels, showed increased levels of IFN-␥ in lung extracts from mice of the resistant DBA/2 strain after a pulmonary challenge, whereas the susceptible BALB/c strain manifested a predominant IL-4 response. The importance of these cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 39 publications
(44 reference statements)
3
51
0
Order By: Relevance
“…18,43,47 The host response of DBA/2 mice has been shown to be directed toward a protective Th1 response, related to interleukin (IL)-12 and interferon-␥ , whereas susceptible BALB/c exhibit a Th2 response, related to IL-4 and IL-10, and less resistance to infection. 34,39,40,48 Additionally, gene knockout mice have proven useful in demonstrating that IL-10 plays a significant role in the susceptibility of the mouse. IL-10 knockouts were more resistant to infection than were normal control mice.…”
Section: Host Responsementioning
confidence: 99%
“…18,43,47 The host response of DBA/2 mice has been shown to be directed toward a protective Th1 response, related to interleukin (IL)-12 and interferon-␥ , whereas susceptible BALB/c exhibit a Th2 response, related to IL-4 and IL-10, and less resistance to infection. 34,39,40,48 Additionally, gene knockout mice have proven useful in demonstrating that IL-10 plays a significant role in the susceptibility of the mouse. IL-10 knockouts were more resistant to infection than were normal control mice.…”
Section: Host Responsementioning
confidence: 99%
“…17 Further studies in mice have shown that increased levels of Th1associated cytokines (IFN-␥ ) correlate with greater resistance while Th2associated cytokines (IL-4) correlate with susceptibility. 11,18 Therefore an adjuvant was selected that would promote a Th1 immune response. Previous studies have demonstrated that CpG adjuvants, including ISS, result in the secretion of Th1 cytokines IFN-␥ and IL-12 and increased vaccine efficacy when used in combination with Montanide ISA-51, a water-in-oil emulsion.…”
Section: Discussionmentioning
confidence: 99%
“…Among different mouse models, BALB/c and C57BL6 mouse strains are susceptible and DBA/2 mouse strain is resistant to coccidioidomycosis. 10,11 The difference in their susceptibility is related to differences in Th1 response against Coccidioides. 11 Similar to mouse strains, it has been established in humans that the susceptibility to coccidioidomycosis is determined by racial or genetic predispositions, age, pregnancy, and immunological status of people in the endemic areas.…”
Section: The Susceptibility To Coccidioides Infection Is Associated Wmentioning
confidence: 99%
“…10,11 The difference in their susceptibility is related to differences in Th1 response against Coccidioides. 11 Similar to mouse strains, it has been established in humans that the susceptibility to coccidioidomycosis is determined by racial or genetic predispositions, age, pregnancy, and immunological status of people in the endemic areas. 6 For example, patients with AIDS, 12 pregnant women, 13 and patients with deficient T cell reactivity 14 are more at risk of developing severe disseminated form of coccidioidomycosis.…”
Section: The Susceptibility To Coccidioides Infection Is Associated Wmentioning
confidence: 99%